PRODUCTIVITY AND ENERGETIC EFFICIENCY OF CULTIVATION OF NEW VARIETIES OF SUDAN GRASS AND SORGHUM-SUDAN HYBRIDS - S. I. Gorpinichenko; G. V. Metlina; S. А. Vasilchenko; N. A. Kovtunova (Зерновое хозяйство России, 2018)
Due to the increasing aridity during the vegetation, productivity of fodder crops is unstable in the last years, and does not meet the cattle needs in rich feed. We can solve the problem by increasing the areas with grass sorghum, which is a promising crop for obtaining green mass and hay. The article has given the study results of productivity and assessment of bio energetic efficiency of cultivation of new varieties of Sudan grass and sorghum-Sudan hybrids. The field trials were conducted from 2011 till 2015 in the laboratory of breeding of fodder sorghum of FSBSI ARRICG after I.G. Kalinenko. In the field trials the soil consisted of chernozem (black soil), carbonate, heavy-loamy, with a humus content in arable layer (3,5%). During the years of study the average productivity of the new variety ‘Krasava’ was 48,8 t/ha of green mass, 11,7 t/ha of dry matter , which was on 15,6% and 14,7% higher than the productivity of the standard variety ‘Aleksandrina’. The productivity of the sorghum-Sudan hybrid ‘Germes’ was 58,6 t/ha of green mass and 13,3 t/ha of dry matter, which was on 9,9% and 9,05 higher than the productivity of the standard hybrid ‘Gustolistny’. The variety ‘Krasava’ and the hybrid ‘Germes’ produced the largest yield of fodder units (10,25 and 12,81 t/ha), digestible protein (0,707 and 0,885t/ha), energy (118,17 and 135,13 GJ/ha), coefficient of energetic efficiency (4,14 and 4,61).